Removal of an Aural Foreign Body by Magnetism - Emily Prentice; Emily Bartlett; Jonathan S. Ilgen (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: A male patient in his thirties with a history of polysubstance use presented to the emergency department (ED) due to an abrasion on his left forehead caused by banging his head against a wall in self-injurious behavior. A non-contrast computed tomography of the head obtained to rule out intracranial injury incidentally demonstrated a radiodense foreign body in the left external ear canal. A round metallic foreign body was subsequently visualized on otoscopic examination. The aural foreign body (AFB) was identified as a metallic bead that the patient had placed into his own ear; however, he reported no associated discomfort, hearing changes, or discharge. Traditional approaches for removing AFBs were considered; however, due to the position and smooth surface of the bead, there was concern they would be unsuccessful. Recognizing the metallic nature of the AFB, the clinician held a ceramic donut magnet adjacent to the patient’s ear and subsequently extracted the AFB without complication or patient discomfort. Discussion: Aural foreign bodies account for a significant number of visits to EDs annually. Removal of AFBs can be challenging, often requiring specialized equipment or specialty referral for management. Using magnetism over short distances for the purpose of extracting metallic AFBs presents a low-cost, low-risk intervention. When used in applicable scenarios, this technique can decrease the need for specialty referral and can especially benefit patients seeking care in less-resourced settings.